Minat Generasi Milenial Menggunakan E-Wallet Link Aja: Perspektif Teori Persepsi dan Perilaku - Violinda, Qristin; Khorunnisya, Nakita Via (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to analyze the effect of perceived convenience, perceived benefits, perceived risk and trust on behavior using the LinkAja e-wallet on Universitas PGRI Semarang students. This study uses quantitative research, namely the results of research in the form of statistical figures. Data collection using a questionnaire, with a convenience sampling sampling technique. The respondents of this study were 106 students of FEB Universitas PGRI Semarang Class of 2017-2020. The results showed that the perception of convenience and trust had a positive and significant effect on behavior using the LinkAja E-Wallet while the perceived benefits and risks had a negative and significant effect on behavior using the LinkAja E-Wallet. The importance of implementing TAM (Technology Acceptance Model) for company management is to maintain the quality of company management which will have an impact on the quality of the company's products. So, later the output of the company can satisfy the expectations of customers. Keywords: perceived ease, perceived benefits, perceived risk, trust, and use behavior